A Transregional Approach in US Policy in the Asia Pacific Region in the Early 1980s - Vladimir Kulikov (Международная аналитика, 2018)
The following article attempts, from the viewpoint of Russian interests, to confirm the thesis of the continuity of long-term approaches of the military-political establishment of the United States to security problems in the Asia – Pacific region, formulated or confirmed in early 1980’s by Ronald Reagan administration, based on the analysis of one of the most significant American collective monographs of that period. Special attention to this well-known work is due to the fact that it, in the author’s opinion, for the first time in a rather concise form reflected the then completed process of understanding of the experience of American participation in the Vietnam war (or in the broader sense of “deep involvement in Asia”), as well as the new role of the so-called “Chinese factor” and traditional allies of the United States by influential representatives of the intellectual military establishment at that time. Despite the inadequacy of this approach to the analysis of deeper socio-economic processes in Northeast Asia (by the way, in the historiography of that time the region was often called the Far East), which determine the main directions and specifics of the situation, the continuity of the scale of priorities of American policy in the AsiaPacific region and commitment to transregional and transit strategies are still significant today. The author suggests that at the present time there is a process of reformulation and bringing in line with the slogans of the “New Americanism” of the agenda of American power policy, which will take into account the tools specified in the work of its implementation in the sphere of “vital interests” of Russia.